(RETRACTED ARTICLE) IMPLEMENTASI PEMBELAJARAN TAHFIDZUL QUR’AN DI MI ISTIQOMAH SAMBAS PURBALINGGA - Bakhron Sodik (Jurnal Penelitian Agama, 2020)
Effective tahfidzul learning of the Qur'an is one of the supporting factors in achieving the goal of forming the values ​​of the Qur'an in students. The purpose of this research is to find a picture of the planning of learning, organizing, mobilizing and implementing, and supervising the learning program of tahfidzul Qur’an at MI Istiqomah Sambas Purbalingga which narrates the memorization of 5 juz of the Qur'an to its graduates. This research uses descriptive method with a qualitative approach. Data collection is done through documentation, observation, and interviews. The subjects in this study were the head of the madrasah and the head of the religious sector and religious staff, and the coordinator of the tahfid at MI Istiqomah Sambas Purbalingga. The results showed that: 1). Planning tahfidzul Qur’an learning is done through the preparation of memorizing tarjets and determining effective weeks and days in each semester. 2). Organizing is done through the distribution of tasks and responsibilities and the structure of tahfidz supporting teachers. 3). The mobilization is carried out through the coordination meeting of the tahfidz coordinator as a shering forum for decision making and directing the tahfidzul Qur’an learning program and the implementation of learning is held every Monday-Friday. 4). Supervision is carried out through assessing teacher performance at the end of December and June. The highest achievement tarjet for the third year of the implementation of the tahfidzul Qur'an program in 2018/2019 is juz 29 and 30, the lowest tarjet for class 1 is juz 30 to Surat al Ghosyiyyah. For class 1, 85% of the target is achieved and 11% of students exceed the target. Class 2 target is 19%. Class 3, 10.86% reached the target and 0.35% of students exceeded the score. Class 4 target reached 12.44%. Class 5 achieved 4.24% target, and the last grade 6 target reached 13.79% and 1.5% of students exceeded tarjet.